2013
DOI: 10.1097/01.prs.0000435317.76381.68
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis for Capsular Contracture

Abstract: This analysis has provided evidence that submuscular placement and textured implants, in addition to other factors, are significant in reducing the incidence of capsular contracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(68 citation statements)
references
References 25 publications
1
66
1
Order By: Relevance
“…8,14,15 In the studies by Namnoum et al 14 and Stevens et al, 15 the risk of capsular contracture was also significantly higher ( p < 0.03) with smooth surface devices versus those having a textured surface, consistent with the low rate of capsular contracture associated with Natrelle 410 breast implants. Device age was also identified as a significant risk factor for capsular contracture in the primary augmentation cohort in the current study ( p < 0.0001), reflecting the small increasing rate of this complication over time.…”
Section: Discussionmentioning
confidence: 79%
“…8,14,15 In the studies by Namnoum et al 14 and Stevens et al, 15 the risk of capsular contracture was also significantly higher ( p < 0.03) with smooth surface devices versus those having a textured surface, consistent with the low rate of capsular contracture associated with Natrelle 410 breast implants. Device age was also identified as a significant risk factor for capsular contracture in the primary augmentation cohort in the current study ( p < 0.0001), reflecting the small increasing rate of this complication over time.…”
Section: Discussionmentioning
confidence: 79%
“…Smaller studies ( n = 183 to 4412) that reported demographic information and surgical characteristics for subjects who underwent breast augmentation show similar baseline characteristics. 1421 For example, several studies reported that subjects who underwent primary breast augmentation were primarily in their mid-30s, with the majority of subjects receiving implant volumes between 300 and 399 cc and implants inserted mainly through inframammary incisions. 1421 In those studies, the majority of subjects were white, married, and had attended college.…”
Section: Discussionmentioning
confidence: 99%
“…1421 For example, several studies reported that subjects who underwent primary breast augmentation were primarily in their mid-30s, with the majority of subjects receiving implant volumes between 300 and 399 cc and implants inserted mainly through inframammary incisions. 1421 In those studies, the majority of subjects were white, married, and had attended college. 14,17,1921 However, implant type, surface, and shape varied between these studies, with two describing round silicone gel implants, 14,20 others describing anatomic silicone gel implants or both types, 17,18,21 and one study directly comparing silicone with saline implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Textured devices are less likely to move but may have benefit in reducing the incidence of capsular contracture. 6 The silicone gel in a round implant is less cohesive than the shaped implants; thus, they are softer. A closed suction drain is sometimes used in cases where extensive capsulotomy, capsulectomy, or capsulorrhaphy has been performed.…”
Section: Methodsmentioning
confidence: 99%